치성 각화 낭종의 술후 재발양상과 추적관찰 기간의 제안 - 박세현(Se-Hyun Park); 김남균(Nam-Kyun Kim); 김기호(Ki-Ho Kim); 강상훈(Sang-Hoon Kang); 박형식(Hyung-Sik Park); 김형준(Hyung-Jun Kim); 차인호(In-Ho Cha); 남웅(Woong Nam) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2008)
Post-operative recurrence of cystic lesion is a great concern for clinician, patients, and their family, especially in case of odontogenic keratocyst, which has aggressive behavior and high recurrence rate. The purpose of this study was to evaluation clinical characters of OKC, focusing of the recurrence rate and proposed critical follow-up period. 58 cases (aged 9 to 66, 33 males and 25 females) of OKC were reviewed for sex of patients, location, size, operative procedure type, radiographic findings, histopathologic findings, post-operative recurrence time, from 2000 to 2005 at Yonsei Medical Center, were selected. The computerized statistical analysis was carried out with SAS system. 18 of 58 cases (31.03%) were recurred and this study revealed no statistically significant difference in recurrence rate for sex, location, size, radiographic findings, histopatologic findings, operative procedure type, recurrence timing. 3 out of 18 cases (16.7%) showed one or more recurrence. This was statistically significant difference (P=.0264). In this study, 15 of 18 cases (83.3%) were observed recurrence during 4 years after removal of the OKCs, we suggest critical follow-up period during 4 years after operation. KCI Citation Count: 2